Effects of salt substitute on urinary electrolytes and blood pressure in a real-world setting—cohort study in Hunan, China - Wu, Hao; Ouyang, Wenbin; Deng, Jing; He, Yongmei; Yin, Lu; Cao, Xia; Chen, Zhiheng; Yang, Pingting; Wang, Yaqin; Li, Ying; Huang, Xin (Frontiers in Nutrition, 2024)
Background and aimsSalt substitute is considered an effective strategy to reduce sodium and increase potassium intake and thereby lower blood pressure in China, but its benefits and risks are uncertain in real-world data. This study is designed to compare the difference in the 1-year efficacy of salt substitute and salt restriction on urinary electrolytes and blood pressure.Methods and resultsA total of 2,929 and 2,071 participants with the 24-h estimated urinary sodium excretion (eUNaE) above 2.36 g/d using salt substitute (SS) and salt restriction (SR) strategies, respectively, were followed for 1 year. Salt substitute users were further divided by potassium chloride (KCl) content (13% vs 25%) and duration (9–11 vs 12 months). The 24-h eUNaE and estimated urinary potassium excretion (eUKE) levels were calculated using the Kawasaki formula from spot urine sample. The SS group (n = 1,897) had lower eUNaE (3.82 ± 1.03 vs 4.05 ± 1.01 g/day, p < 0.01) than the SR group (n = 1,897) after 1 year. Both 13 and 25% KCl substitutes reduced eUNaE versus restriction (p < 0.05). The SS group had a higher eUKE than the SR group (2.09 ± 0.43 vs 1.71 ± 0.62 g/day, p < 0.01). The eUKE was higher with 25% versus 13% KCl substitutes, while the Na/K was lower with 25% versus 13% KCl substitutes (p < 0.05). No significant blood pressure differences occurred between the SS and SR groups (p > 0.05), whereas 25% KCl exposure was related to a lower level of SBP, regardless of whether it was compared with SR or 13% KCl.ConclusionCompared with salt restriction, salt substitute results in more sodium reduction and greater potassium increase. In spite of this, it does not result in better control of blood pressure, especially for the group receiving 13% KCl.